Overcoming anxiety - McNeilly, Robert; Centre of Effective Therapy (Firm) (Brighton North, Vic. : Centre of Effective Therapy, 2005)
This program on overcoming anxietyhelps clients to effectively reconnect with their preferred experiences in a time effective way, rather than focusing on what is wrong
Title on booklet: Learning solution in hypnosis & counselling
Psychologist: Dr. Robert McNeilly
Keywords: Anxiety -- Treatment; Anxiety -- Case studies